PENGARUH BRAND AWARENESS, BRAND IMAGE, DAN TRUST TERHADAP MINAT GENERASI Z MENGGUNAKAN APLIKASI WONDR BY BNI - Yuningsi, Yuningsi; Lubis, Kartika Sari (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The rapid growth of financial technology (fintech) has prompted banks to innovate, one of which is through digital applications like WONDR by BNI. Generation Z, as digital natives, represents a promising market segment but is highly selective. Their interest in adopting an application is significantly shaped by their perceptions of the brand. This study examines the simultaneous and partial effects of Brand Awareness (X1), Brand Image (X2), and Trust (X3) on Generation Z's Interest (Y) in using the WONDR by BNI application. Data were gathered through an online survey involving 125 Generation Z respondents who were either aware of or had used the WONDR app, selected using purposive sampling. The data were analyzed using multiple linear regression with SPSS software to assess the impact of independent variables on the dependent variable, tested through t-tests (partial) and F-tests (simultaneous). The results revealed that, simultaneously (F-test), all three independent variablesBrand Awareness, Brand Image, and Trusthad a significant effect on Purchase Interest. Individually (t-test), each of the independent variables was found to have a significant and positive influence on Generation Z's interest. The standardized regression coefficients (Beta) indicated that Trust (X3) was the most influential variable (Beta = 0.511; sig. 0.000), followed by Brand Image (X2) (Beta = 0.487; sig. 0.000), and Brand Awareness (X1) (Beta = 0.388; sig. 0.000). These findings conclude that Brand Awareness, Brand Image, and Trust, both collectively and individually, significantly influence Generation Z's interest in using the WONDR by BNI application.Keyword: Brand Awareness, Brand Image, Trust, Interest Generation ZAbstrak: Pertumbuhan pesat teknologi keuangan (fintech) telah mendorong bank untuk berinovasi. Salah satu contohnya adalah pengembangan aplikasi digital seperti WONDR oleh BNI. Sebagai generasi digital, Generasi Z mewakili segmen pasar yang menjanjikan dan sangat selektif. Keputusan mereka untuk mengadopsi suatu aplikasi sangat dipengaruhi oleh persepsi mereka terhadap merek. Penelitian ini menganalisis efek simultan dan parsial dari brand awareness (X1), brand image (X2), dan trust (X3) terhadap Minat Generasi Z (Y) dalam menggunakan aplikasi WONDR oleh BNI. Data dikumpulkan melalui survei online terhadap 125 responden aGenerasi Z yang mengetahui atau pernah menggunakan aplikasi WONDR. Responden ini dipilih menggunakan metode sampling purposif. Analisis regresi linier berganda dilakukan menggunakan SPSS untuk menilai dampak variabel independen terhadap variabel dependen, dengan efek diuji melalui uji t (parsial) dan uji F (simultan). Hasil menunjukkan bahwa ketiga variabel independen: brand awareness, brand image, trust memiliki pengaruh signifikan terhadap minat menggunakan secara simultan (uji F). Secara individu (uji t), setiap variabel independen ditemukan memiliki pengaruh positif yang signifikan terhadap minat Generasi Z. Koefisien regresi standar (Beta) menunjukkan bahwa trust (X3) adalah variabel yang paling berpengaruh (Beta = 0.511; sig. 0.000), diikuti oleh brand image (X2) (Beta = 0.487; sig. 0.000) dan brand awareness (X1) (Beta = 0.388; sig. 0.000).Kata kunci: Brand Awareness, Brand Image, Trust, Minat Menggunakan